Analysis for improving performance : tools for diagnosing organizations and documenting workplace expertise - Swanson, Richard A., 1942- (Publication in the Berrett-Koehler organizational performance series., 2007)
This revised and expanded version of Analysis for Improving Performance provides the tools for doing the crucial - yet often overlooked - upfront analyses essential to the success of any performance improvement effort. Human resource development expert Richard A. Swanson's step-by-step method allows program developers and managers to: assess an organization's real business needs and the status of its supporting systems; analyze necessary worker skills, knowledge, and attitudes; specify performance requirements and evaluation standards; and produce a viable and comprehensive performance improvement design. This second edition is extensively revised throughout and contains many updated case studies and expanded concepts. It also contains a new chapter on Documenting and Improving Work Process. In the end, the tools and resources provided within Analysis for Improving Performance will help make sure that workplace performance improvement efforts really work.